2016
DOI: 10.1016/j.juro.2016.03.152
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings and Treatment Outcomes in Patients with Extraprostatic Extension Identified on Prostate Biopsy

Abstract: Purpose To describe the histopathological, clinical and imaging findings among men with extraprostatic extension (EPE) on prostate biopsy. Materials and methods We searched our Institutional Pathology Database, between the years 2004-2015, for pathology reports detailing EPE on prostate biopsy in untreated patients. Patient characteristics, biopsy features, imaging interpretations and outcomes were examined. Results Of 19,950 patients with prostate cancer on biopsy, 112 had EPE, a prevalence of 0.6% (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…However, due to its rarity on biopsy, little is known about biopsy detected EPE as a potential independent predictor of aggressive PCa. In a study by Fleshner et al , 112/19,950 (0.6%) patients with PCa on SB had detection of EPE ( 1 ). Overall, we found EPE and/or SVI in 1.5% of patients with PCa who had undergone TB.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, due to its rarity on biopsy, little is known about biopsy detected EPE as a potential independent predictor of aggressive PCa. In a study by Fleshner et al , 112/19,950 (0.6%) patients with PCa on SB had detection of EPE ( 1 ). Overall, we found EPE and/or SVI in 1.5% of patients with PCa who had undergone TB.…”
Section: Discussionmentioning
confidence: 97%
“…Identification of EPE is an important component of staging in PCa patients, and is defined by the American Joint Committee on Cancer (AJCC) TNM staging system as pT3a in the presence of extension into the periprostatic fat and as pT3b in the case of SVI ( 1 , 15 , 16 ). Although the presence of EPE on SB is a rare occurrence, a significant number of patients who undergo radical prostatectomy for presumed localized disease are found to have EPE, implying that its presence is being consistently under detected on SB ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only two studies have reported the outcomes of patients with EPE on needle biopsy. 6 7 Miller et al . 7 from John Hopkins University (JHU) reviewed 51 891 cases of prostatic adenocarcinoma from 1997 to 2009 and reported a prevalence of positive EPE on needle biopsy of 0.19%.…”
Section: Discussionmentioning
confidence: 99%
“…However, because it is relatively rarely detected, there is limited information on the clinical significance of biopsy-detected EPE in patients with PCa. 6 7 In addition, neither the detection rate of EPE in metastatic PCa (mPCa) nor its clinical outcomes have yet been reported.…”
Section: Introductionmentioning
confidence: 99%